Estrobolome dysregulation is associated with altered immunometabolism in a mouse model of endometriosis - Alghetaa, Hasan; Mohammed, Amira; Singh, Narendra P.; Bloomquist, Ryan F.; Chatzistamou, Ioulia; Nagarkatti, Mitzi; Nagarkatti, Prakash (Frontiers in Endocrinology, 2023)
Endometriosis is a painful disease that affects around 5% of women of reproductive age. In endometriosis, ectopic endometrial cells or seeded endometrial debris grow in abnormal locations including the peritoneal cavity.Common manifestations of endometriosis include dyspareunia, dysmenorrhea, chronic pelvic pain and often infertility and symptomatic relief or surgical removal are mainstays of treatment. Endometriosis both promotes and responds to estrogen imbalance, leading to intestinal bacterial estrobolome dysregulation and a subsequent induction of inflammation. In the current study, we investigated the linkage between gut dysbiosis and immune metabolic response in endometriotic mice. Ovariectomized BALB/c mice received intraperitoneal transplantation of endometrial tissue from OVX donors (OVX+END). Control groups included naïve mice (Naïve), naïve mice that received endometrial transplants (Naive+END) and OVX mice that received the vehicle (OVX+VEH). Colonic content was collected 2 weeks post-transplantation for 16s rRNA pyrosequencing and peritoneal fluid was collected to determine the phenotype of inflammatory cells by flow cytometry. We noted a significant increase in the number of peritoneal fluid cells, specifically, T cells, natural killer (NK) cells, and NKT cells in OVX+END mice. Phylogenetic taxonomy analysis showed significant dysbiosis in OVX+END mice, with an increase in abundance of Phylum Tenericutes, Class Mollicutes, Order Aneroplasmatales, and Genus Aneroplasma, and a decrease in Order Clostridiales, and Genus Dehalobacterium, when compared to OVX+VEH controls. The metabolomic profile showed an increase in some tricarboxylic acid cycle (TCA)-related metabolites accompanied by a reduction in short-chain fatty acids (SCFA) such as butyric acid in OVX+END mice. Additionally, the mitochondrial and ATP production of immune cells was enforced to a maximal rate in OVX+END mice when compared to OVX+VEH mice. Collectively, the current study demonstrates that endometriosis alters the gut microbiota and associated immune metabolism.